(untitled) (Comparatismi, 2025)
The study of the dialectical relationship between ‘forms and genres’ opens up interesting perspectives that look at the complexity of the work’s creation and highlight fundamental aspects of the genre system, from both a diachronic and synchronic perspective. Particularly significant in this regard are studies on the ‘short form’, which have become increasingly widespread in recent decades. The short form interferes with multiple genres, crossing them transversally. By reviewing and discussing the results of research on this interaction, this contribution aims to highlight its many contributions and different perspectives for analysis.